Chabani Manganyi’s memoir - Hayes, Grahame (PINS-Psychology in Society, 2016)
Chabani Manganyi’s memoir, Apartheid and the making of a Black psychologist, was launched in June this year, at Circa Gallery in Rosebank, Johannesburg. The invited speaker at this event was Grahame Hayes. Wits University Press then organised another launch event, in conjunction with WiSER (Wits Institute for Social & Economic Research), and the Department of Psychology, which was held at WiSER on 24 August 2016. The speakers at this event - Catherine Burns (WiSER), Garth Stevens (Dept of Psychology - Wits), and Hlonipha Mokoena (WiSER) - were asked to discuss Manganyi’s memoir under the rubric, “Being black in the world: Race, memory and the psychology of Black subjectivity in the memoir of Chabani Manganyi”.